IMPLEMENTASI KONSEP KEPEMIMPINAN DEMOKRATIS DI MI MUHAMMADIYAH LEMAHDADI - Muhammad Idris Maas Zaid; Fajar Dwi Mukti (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2019)
This study aims to describe the implementation of democratic concepts in MI Muhammadiyah Lemah Dadi Bantul. This research uses descriptive approach of skin. The subject of this research is the principal and teachers of MI Muhammadiyah Lemah Dadi. Data analysis techniques in this study begins with the presentation of data, namely the presentation of data obtained in the field. After that, data reduction, which is choosing and sorting the required data and then continued with the verification, the data inferred according to the problem under study. Based on the results of this study shows the implementation of the concept of democratic leadership in MI Lemah Dadi Bantul, conducted by finding the foundation of philosophy, drafting the concept, mechanism implementation, and find the advantages and disadvantages of the concept of democratic leadership and can be a concept in the application of democratic leadership in their respective institutions.